Audit Delay and Influencing Factors: The Role of Leverage, Public Ownership, and Going Concern Opinions - Trisanti, Theresia (Equity: Jurnal Akuntansi, 2025)
This study empirically examines the effect of leverage levels, public ownership, and going concern audit opinions on audit delay. The research employs a purposive sampling method, with a final sample consisting of 33 mining companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. Multiple regression analysis is used to test the hypotheses. The findings indicate that leverage levels have a positive impact on audit delay, suggesting that higher financial risk leads to prolonged audit processes. However, public ownership does not significantly influence audit delays. Additionally, the issuance of a going concern audit opinion is associated with longer audit delays. These results contribute to the understanding of factors affecting audit timeliness in the mining sector.